Institutional Trust and Subjective Well-Being in Post-Soviet Countries - Bekhzod Egamberdiev; Ihtiyor Bobojonov; Lena Kuhn (Comparative Economic Studies, 2025)
Post-Soviet countries have still been experiencing a transition in governance and institutional performance. However, such transitions are not always explained by citizens' high institutional trust, reflecting on their subjective well-being. One of the objectives of the study is to identify a typology of institutional trust using a post-Soviet context. We use the Life in Transition dataset by the European Bank for Reconstruction and Development for twelve transitional countries. We apply a three-step approach for Latent Profile Analysis (LPA) in the estimation strategy. Using LPA with 11-item scale questions for subjective well-being, we obtain “Low Satisfaction”, “Medium Satisfaction”, and “High Satisfaction” homogenous profiles. Using Principal Component Analysis (PCA) with 14 personal statements, we also measure institutional trust towards the performance of institutions. The relationship between institutional trust and life satisfaction profiles indicates that the "Medium Satisfaction" and "High Satisfaction" classes, compared to the "Low Satisfaction" profiles, are positively associated with higher institutional trust. We also analyse the effect of institutional trust on life satisfaction through corruption. The findings confirm a positive effect of institutional trust on life satisfaction.
Keywords: I18; J17; O15; P20; 330; Institutional trust; Corruption; Life satisfaction; Post-Soviet; Latent Profile Analysis